Artificial Intelligence (Online Resource): A panacea for SMEs in healthcare - ANUJ KUMAR; Asif Ali Syed; Anoop Pandey (ACHSM, 2021)
This paper presents a review of the most recent and popular research papers on the use of artificial intelligence in the healthcare sector. SMEs consist of 60-65% of Indian medical device market. Many doctors are operating through private hospitals which come under the category of SMEs segment. Technology is proving to be a boon for all the sectors, artificial intelligence an emerging technology has the potential to change the fortune of SMEs in health care sector. In this paper, there will be discussion on how artificial intelligence can help the healthcare sector in different ways. SMEs working in healthcare can take a learning from this paper and can utilize it for betterment. (*The paper was presented at the AICTE International Conference on Circular Economy, Management and Industry, Bharati Vidyapeeth's Institute of Management Studies and Research, Navi Mumbai and Apeejay School of Management, Dwarka, Delhi, India. October 2021)